2012
DOI: 10.1603/en12180
|View full text |Cite
|
Sign up to set email alerts
|

Arboreal Insects Associated With Herbicide-Stressed <I>Pinus resinosa</I> and <I>Pinus sylvestris</I> Used as <I>Sirex noctilio</I> Trap Trees in New York

Abstract: In September of 2004, Sirex noctilio F. (Hymenoptera: Siricidae) was detected in New York State and later found to be established over a larger area, including parts of southeastern Canada and the northeastern United States. A key component of S. noctilio detection and management plans in other parts of the world where S. noctilio has become established are chemically girdled trap trees. Trap tree usage in North America is confounded by the presence of diverse communities of organisms that inhabit dead and dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…The region of eastern North America invaded by S. noctilio is even more diverse with respect to woodborer diversity: published records indicated 29 species of Cerambycidae and 9 species of Buprestidae, 7 and 1 of which could be described as common (Table 4). Dodds et al [63] found 20 species of Cerambycids associated with Sirex trap trees near Syracuse, NY. In comparison to Europe and North America, pine forests of the Southern Hemisphere are dramatically depauperate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The region of eastern North America invaded by S. noctilio is even more diverse with respect to woodborer diversity: published records indicated 29 species of Cerambycidae and 9 species of Buprestidae, 7 and 1 of which could be described as common (Table 4). Dodds et al [63] found 20 species of Cerambycids associated with Sirex trap trees near Syracuse, NY. In comparison to Europe and North America, pine forests of the Southern Hemisphere are dramatically depauperate.…”
Section: Resultsmentioning
confidence: 99%
“…They would clearly be released from such competition in the Southern Hemisphere (Table 5). This would be a favorable scenario for North America, where the diversity of xylophagous insects in pines is comparable to Europe (Table 4; [63]). However, more detailed patterns of occupancy within host trees failed to support a strong role for interspecific competition in determining the abundance of S. noctilio in Galicia.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are large ecological differences between the invaded regions of North America and those of the Southern Hemisphere, which confound attempts at meaningful comparison. Specifically, North America is host to a diverse guild of other pine‐colonising insects, including cerambycid, buprestid, and curculionid beetles, as well as other native siricids (Dodds et al ., ). In North America, S. noctilio has caused limited tree mortality, primarily attacking suppressed Pinus resinosa Aiton, a native pine, and Pinus sylvestris L., a naturalised pine from Europe (Dodds et al ., ; Ayres et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Some species of ambrosia beetles, including Xylosandrus germanus, have been captured in higher numbers in traps lower than the trapping height used in our study [62]. However, these species have also been captured at relatively high numbers on forest trees at heights between 1.5 m and 6 m in previous studies [63,64]. No ambrosia beetle attacks were found at or below our trapping height during tree surveys, so it is unlikely that our trapping methods significantly underestimated these species.…”
Section: Discussionmentioning
confidence: 61%